2013
DOI: 10.4236/msa.2013.411085
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solid State Nitric Oxide Sensor Using Siloxane-Poly(Oxypropylene) (PPO)

Abstract: In this paper, a novel solid state Nitric Oxide (NO) sensor made of a spin trap (iron(II)-diethyldithiocarbamate complex, FeDETC) encapsulated in a siloxane-poly(oxypropylene) (PPO) matrix was developed. Nitric oxide (NO), a free radical molecule, has numerous roles in various physiological functions, such as the regulation of blood pressure, immune response to bacterial infection, and nervous systems. Siloxane-polyether hybrid materials, for example siloxanepoly(oxypropylene) (PPO), are easy to prepare, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Herculano et al [ 74 ] showed that the release of nitric oxide (NO) could be improved when incorporated in ureasil-PPO ( M w 400 g·mol −1 ). NO is a free radical indicated for the treatment of blood vessel protection.…”
Section: Applications Of Organic-inorganic Hybrids Materials In Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Herculano et al [ 74 ] showed that the release of nitric oxide (NO) could be improved when incorporated in ureasil-PPO ( M w 400 g·mol −1 ). NO is a free radical indicated for the treatment of blood vessel protection.…”
Section: Applications Of Organic-inorganic Hybrids Materials In Drmentioning
confidence: 99%
“…Thus, the authors use encapsulation of iron(II)-diethyldithiocarbamate (FeDETC) in various matrices for either the measurement of NO or its release due to the affinity between NO and the iron complexes, allowing the use of electron paramagnetic resonance (EPR) to radical detection [ 77 ]. The studies showed that it was possible to detect the release of NO after 40 days [ 74 ]. This system is an important advance in the development of DDS containing NO for the treatment of heart diseases.…”
Section: Applications Of Organic-inorganic Hybrids Materials In Drmentioning
confidence: 99%